Otimização do diagnóstico micológico e abordagem epidemiológica de dermatomicoses analisadas no laboratório do Posto Médico de Guarnição de Belo Horizonte-MG - Luciane de Paula Santos Vieira (2021)
Fungal infections have a great implication in the population’s health and quality of life, generally with unsatisfactory treatments, and they are seen as an aesthetic problem and often neglected. In the last decades, there was an increase in the prevalence of these infections, due to the high incidence of immunodeficiencies, immunossupressive therapies and age of the population, combined with improved medical care in general. This increase is probably more pronounced than epidemiological surveys show, mainly due to the lack of mycological diagnosis. Improved medical care, increased requests for mycological diagnosis, as well as the optimization of the methodologies for the isolation and identification of fungi in clinical laboratories are essential to improve patient care and reduce costs related to failure of empirical treatment. In this context, the objective of this study was to optimize the methodologies used in mycological diagnosis and to conduct an epidemiological study of dermatomycosis, in outpatient care at the Mycology Laboratory of the Posto Médico de Guarnição, in Belo Horizonte, Brazil. Through patients’ anamnesis, it was possible to trace the epidemiological profile related to age, gender and underlying pathology, as well as the location of the lesion, direct examination result and fungal culture, from September 2019 to November 2020. Seventy-six patients were analyzed, of which 43 were female, representing 56.58%. Of the total number of patients, 27.63% are active people in relation to occupation, followed by 21.05% of pensioners. Among the main health/activity problems, we have sports practice corresponding to 30.26% and 27.63% corresponding to local trauma. The most used material was subunual shaved hallux, right and left, corresponding to 25,77%, respectively. Of the 163 direct mycological tests, 120 were positive (73.62%) and 89 of the fungal culture results (54.60%) were positive. Our studies reaffirm that the adequate and optimized routine service of mycological diagnosis helps clinical practice generating more accurate and reliable diagnosis for the patient, and in the prescription of appropriate treatment to each clinical picture. In addition, epidemiological data may assist in delineating prophylactic strategies with an impact on the community.